Tax and Welfare Reforms in the Czech Republic-Structural Implications and Challenges - Dalsgaard, Thomas (IMF Working Papers; Working Paper ;, 2008)
The paper provides an analysis and discussion of key structural implications of the 2007 and 2008 welfare and tax reforms in the Czech Republic. Based on a detailed micro-study of marginal and average effective tax rates for individuals at various points along the earnings curve, it concludes that while incentives to save and invest have improved, work incentives are being severely hampered by high marginal effective tax rates for low- and middle income individuals. The reforms also fail to address the most pressing fiscal concern: to put government finances on a sustainable path.